Revolutionizing Supply Chains: Unleashing Reconfigurability and Flexibility through Industry 4.0 Integration - ACEVEDO AMAYA, MARIO ROBERTO; ORTEGA-JIMENEZ, CESAR H. (LACCEI, 2024)
In response to dynamic market demands, supply chains are undergoing a transformative shift towards heightened flexibility through the reconfiguration of manufacturing processes. Industry 4.0 has emerged as a pivotal avenue for companies seeking to expedite this transformative journey. Nevertheless, the precise role of Industry 4.0 in enhancing the reconfigurability of manufacturing systems remains an evolving area of investigation. This study aims to comprehensively assess the impact of Industry 4.0 on both the reconfigurability and flexibility of supply chains, focusing on identifying critical dimensions of manufacturing system reconfigurability that contribute to supply chain flexibility. Empirical insights were derived from an extensive study involving 309 High-Performance Manufacturing (HPM) project companies across 14 countries. Each research hypothesis was rigorously tested using statistical mediation models and hierarchical regression analysis. The analysis of collected data demonstrated commendable levels of reliability. The findings indicate that the identified dimensions of reconfigurability significantly account for more than 45% of the observed flexibility in the supply chain. This relationship is partially mediated by the extent of applying Industry 4.0 technologies, strategies, and tools.